2020
DOI: 10.1136/bmjopen-2019-033844
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of breathing exercises, foot reflexology and back massage (BRM) on labour pain, anxiety, duration, satisfaction, stress hormones and newborn outcomes among primigravidae during the first stage of labour in Saudi Arabia: a study protocol for a randomised controlled trial

Abstract: IntroductionLabour pain is among the severest pains primigravidae may experience during pregnancy. Failure to address labour pain and anxiety may lead to abnormal labour. Despite the many complementary non-pharmacological approaches to coping with labour pain, the quality of evidence is low and best approaches are not established. This study protocol describes a proposed investigation of the effects of a combination of breathing exercises, foot reflexology and back massage (BRM) on the labour experiences of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 73 publications
1
20
0
3
Order By: Relevance
“…The principal investigator is a certified complementary therapist 27 who designed and trained all research assistants (research coordinators, massage therapists, and outcome assessors) until they were found competent for their tasks in a pilot study. The research coordinators were to educate the pregnant women, explain the study, and obtain consent from the potential participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal investigator is a certified complementary therapist 27 who designed and trained all research assistants (research coordinators, massage therapists, and outcome assessors) until they were found competent for their tasks in a pilot study. The research coordinators were to educate the pregnant women, explain the study, and obtain consent from the potential participants.…”
Section: Methodsmentioning
confidence: 99%
“…There are several theories that support the mechanisms of BRM on pain and labor outcomes which we have elaborated in the protocol study. 27 Briefly stating, the physiological mechanisms of deep-breathing exercises stimulate the parasympathetic nervous system which improves blood circulation, releases endorphin, and decreases the heart rate. It also helps pregnant women to focus on their breathing instead of their uterine contractions, thus helping them to keep calm.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of breathing techniques to control anxiety have been approved in various groups, including, burn patients [10], women with multiple sclerosis [11], obstetrics [12], coronary artery disease [13],…”
Section: Discussionmentioning
confidence: 99%
“…In order to consider ethical J Nurs Explor 2021 Jan;1(1):7 . https://doi.org/10.29252/jnexp.1.1.11 12 issues, the objectives of the study were explained to the patients and the consent form was achieved. .…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Se cree que la colonización microbiana del intestino humano es responsable de la programación concurrente de nuestro sistema inmune y del desarrollo simultáneo del tracto intestinal y del metabolismo asociado. Debe producirse un diálogo continuo entre la microbiota y el huésped para orquestar estos procesos fisiológicos (25) .…”
Section: Desarrollo Del Temaunclassified